Financing costs and development - Tiago Cavalcanti; Joseph Paul Kaboski; Bruno Silva Martins; Cézar Santos (Inter-American Development Bank (IDB), 2023)
Most aggregate theories of financial frictions model credit available at a cost of financing equal to the savings rate but rationed. However, using a comprehensive firm-level credit registry, we document both high levels and high dispersion in ex post credit spreads to Brazilian firms. We develop a quantitative dynamic general equilibrium model in which dispersion in spreads arises from intermediation costs and market power. Calibrating to the Brazilian data, we show that, for equivalent levels of external financing, spreads have profound impacts on aggregate development indeed moreso than credit rationing does and spreads yield firm dynamics that are more consistent with observed patterns.
Keywords: O11; O16; E22; 330; Financial frictions; Credit spreads; Aggregate misallocation